Analysis of vanillin by TLC and HPLC-PDA in herbal material and tincture from Vanilla planifolia Jacks ex. Andrews - Rhayanny Assunção Ferreira, Magda; Schwanz, Melissa; Pereira Cosenza, Gustavo; Teresinha Henriques, Amelia; Soares, Luiz Alberto Lira (Drug Analytical Research, 2026)
Vanilla planifolia (Orchidiaceae) is a species that is renowned globally and represents the largest source of vanillin flavoring used in the food, cosmetic and pharmaceutical industries. This study was carried out to analyze by TLC and HPLC-PDA vanillin in herbal drug and tincture from V. planifolia. The herbal drug was obtained with hydroalcoholic solution under reflux; and a kinetic reaction was performed by TLC. The influences of solvent and herbal drug concentration were studied through an experimental design. The solutions (herbal drug, tincture and standard – vanillin) were prepared and analyzed in HPLC coupled with DAD detector, using wavelength of 280 nm. The total extraction of vanillin was achieved after three extraction cycles, using 1.0 g of herbal material and Ethanol 50% (v/v) as solvent. The method was linear (R2> 0.99) and demonstrated repeatability (RSD < 0.90), intermediate precision (RSD < 1.09), recovery (93.12-113.74%), as well as robustness (RSD < 4.33). The total content of vanillin found was 1.82 g% and 0.21 g% for herbal drug and tincture, respectively. A simple and optimized method for sample preparation by reflux was able to provide the exhaustive extraction of vanillin and does not compromise the reliability of the HPLC-PDA method. The chromatographic procedure was validated to separate and quantify vanillin in herbal material and tincture from pods of V. planifolia.